Correlation Between MCH Book Utilization and Pregnant Women’s Knowledge of Pregnancy Danger Signs at Telaga Dewa Health Center - Aufanisa Putri Utami; mariati mariati; Lela Hartini; Rialike Burhan (Proceeding of Banten Internasional Conference on Health Advancement and Research, 2026)
Pregnancy is a critical phase in a woman’s life cycle and may be accompanied by complications that threaten maternal and fetal health. The Maternal and Child Health (MCH) Handbook, known in Indonesia as Buku KIA, functions as both a documentation tool and an educational medium for pregnant women. However, its utilization remains suboptimal, and many mothers still lack adequate knowledge of pregnancy danger signs. This study aimed to examine the relationship between the use of the MCH Handbook and pregnant women's knowledge of danger signs during pregnancy in the Telaga Dewa Health Center area, Bengkulu City, in 2025. A quantitative analytical survey with a cross-sectional design was conducted among 73 pregnant women selected through total sampling. Data were collected using structured questionnaires and analyzed using univariate and bivariate analysis, with a Chi-square test applied at a 95% confidence level. Results showed that 58.9% of respondents used the MCH Handbook, while 41.1% did not. Additionally, 52.1% of respondents demonstrated poor knowledge of pregnancy danger signs. Bivariate analysis confirmed a significant association between MCH Handbook utilization and maternal knowledge (p = 0.000). In conclusion, the MCH Handbook significantly contributes to improving maternal knowledge regarding pregnancy danger signs. Strengthening mothers’ engagement with the handbook and ensuring continuous support from health workers are recommended to optimize its effectiveness.